Ancient Georgian Versions of the Old Testament - Blake, Robert Pierpont (Harvard theological review, 1926)
One of the most important questions in ancient Georgian literature has to do with the old Georgian versions of the Bible. The problems in this field are very complex. Not only is the history of the translation of the Old Testament entirely distinct from that of the New, but in each of them the translations were made by various hands from different languages and different types of text.